3D LASER SCANNING OF HISTORIC MOLDS FOR DOCUMENTING THE RICHARD-GINORI FACTORY COLLECTION. Issue 3 (August 2014) - Balleri, Rita; Di Tondo, Sergio; Adembri, Giulia; Gherardelli, Monica
Abstract : This paper illustrates the use of three-dimensional (3D) laser scanning to produce virtual models from plaster piece molds of the Richard-Ginori porcelain factory (Sesto Fiorentino, Italy). This study was carried out as part of a long-term project to document the artifacts of the factory including porcelain sculpture, models in wax, terracotta, and plaster, as well a collection of several thousand plaster piece molds dating from the mid-18th to the early 20th century. The objects contained inside the molds are often not recognizable as the molds are made up of several pieces and the internal surfaces are, of course, in negative. Previously, the identification of the molds' subject matter has been limited to recasting porcelain models to produce positives. This time-consuming process can compromise the preservation of the molds. Virtual reconstruction using 3D laser scanning was applied to a set of plaster molds for a statuette called the Giant. Comparison of the virtual reproduction to the original model in terracotta demonstrated it was a faithful copy. The method described in this paper proves that identification of the subject and preservation of the molds are possible with numerous benefits over the traditional process for producing finished porcelain artifacts.